Association between perceived exertion and executive functions with serve accuracy among male university tennis players: A pilot study - Kuroda, Yuta; Ishihara, Toru; Mizuno, Masao (Frontiers in Psychology, 2023)
Serve in tennis is a very important strokes and is positively correlated with the rankings of the Association of Tennis Professionals ranking. This study investigated the associations between time-course changes in the ratings for perceived exertion, executive function, and second serve accuracy during 30-minutes tennis exercise sessions. Eleven Japanese male tennis players participated in the study, and their executive function and second serve performance were evaluated using the paper version of the Stroop Color and Word Test, followed by a serve performance test. The participants took part in a 30-minutes tennis exercise program and performed the Stroop Color and Word Test, heart rate (HR) check, and second serve accuracy test before and after the tennis exercise. Pearson correlation was used to determine the relationships between the ratings for perceived exertion, interference scores on Stroop Color and Word Test performance, and second serve performance. Post exercise, the rating of perceived exertion tended to correlate with serve accuracy (r=-0.57, p=0.07) and interference score (r=0.65, p=0.03). The pre-to-post changes in second serve accuracy were negatively associated with the changes in interference score (r =- 0.54, p=0.08) and interference score in the posttest (r =- 0.73, p=0.01). The results suggest that time-course changes in executive function when playing tennis are positively associated with the accuracy of the second serve. These findings expand the previous knowledge regarding the positive association between time-course changes in executive functions and percentage of points won when playing tennis by including more specific skills (i.e., second serve accuracy).